Nexus between agriculture productivity and carbon emissions a moderating role of transportation; evidence from China - Wang, DanHui; Hussain, Rana Yassir; Ahmad, Ilyas (Frontiers in Environmental Science, 2023)
This research investigates the nexus existing between agricultural productivity and CO2 emissions under the moderating effect of transportation within the context of China. The data for this study are drawn from the World Bank and cover the period 1991-2019. The data is analyzed using an autoregressive distributed lag approach (ARDL). Agricultural productivity is measured in terms of crop and livestock production. The goal of this research is to make some contributions, as crop production has a negative impact on carbon dioxide emissions in the long and short run. Carbon dioxide emissions are positively influenced by livestock production in the long run, but negatively in the short run. As for the moderation effect, the results indicate that transportation significantly impacts agricultural productivity and CO2 in both the long and short term. In addition to discussing the crucial implications, future directions are also discussed.